2017
DOI: 10.1007/s11223-017-9903-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Inconel 718 Surface Treatment by Edge Robotic Deburring with Force Control

Abstract: We present the results of investigations into the application of robotics for deburring and chamfering to a predefined geometric quality. The robotic application was used for a part of the manufacturing process of an aircraft engine detail. Aircraft engine diffuser machining requires manual deburring of many edges. Finishing by hand results in several non-conforming quality details for each diffuser. This paper presents the concept of edge deburring with a controlled force progression pneumatic tool. A specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Exemplary reviews of robotic cutting may be found in Łygas and Danilczuk [1] and Song et al [2]. Algorithms controlling force and their utilisation in processes are found in Refs [3][4][5][6]. Technological parameters' super vision and communication between many robots have been described in Refs [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Exemplary reviews of robotic cutting may be found in Łygas and Danilczuk [1] and Song et al [2]. Algorithms controlling force and their utilisation in processes are found in Refs [3][4][5][6]. Technological parameters' super vision and communication between many robots have been described in Refs [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The number of industrial applications, in which robots come in contact with the environment and where it has a significant influence on the robotised processes realisation quality, is constantly increasing ( Mendes and Neto, 2015). The aforementioned processes include, among others, robotised mechanical processing such as grinding (Zhu et al, 2015), polishing (Gracia et al, 2018;Tian et al, 2016), or edge deburring (Burghardt et al, 2017b). Therefore, modelling and control of robots in interaction with the environment becomes crucial, particularly if the actual features of the environment are taken into account, such as flexibility or damping.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a review of burr formation modeling and control, and factors governing milling burr formation were presented [24]. Robotic application of edge deburring with a controlled force progression pneumatic tool for a part of the manufacturing process of an aircraft engine detail was investigated [25]. A flexible robot-based cast iron deburring cell using a single-point laser displacement sensor was developed for small batch production of a robotized deburring task in a standard cast iron foundry scenario [26].…”
Section: Introductionmentioning
confidence: 99%
“…A set of optimal process parameter combination for robotic machining and the effect of process parameters such as spindle speed, feed rate and tool path strategies on the performance characteristics were investigated using the Taguchi-Grey relational approach and analysis of variance [33]. Edge robotic deburring with a controlled force progression pneumatic tool, as well as a methodology used to select and optimize the edge robotic deburring process, was presented [25]. A sliding mode control method based on radial basis function neural network was proposed for the deburring of industry robotic systems, without the requirements for strict constraints, an accurate model and exact parameters [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation